Evaluation of bcl-2 protein expression and 14;18 translocation as prognostic markers in follicular lymphoma. - Pezzella, F; Jones, M; Ralfkiaer, E; Ersbøll, J; Gatter, K; Mason, D (1992)
Conflicting results have been published on the prognostic significance of t(14;18) in follicular lymphoma: Yunis et al. (1989) reported that its presence indicated poor response to therapy and short survival, whereas Levine et al. (1988) showed no difference in prognosis between cases with and without the translocation. However these results were based on small series of cases and on follow-up periods (no longer than 7 years) which are relatively short for a disease with such a slow clinical evolution. Here we report an investigation of 70 cases of follicular lymphoma with long term follow-up data (up to 17 years). This series has been studied for the presence of the 14;18 translocation and for the expression of bcl-2 protein. Our results show that there are no grounds for considering either the 14;18 translocation or the expression of the bcl-2 protein to be useful prognostic markers in clinical practice.